2002
DOI: 10.1086/340743
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self‐Reporting of Episodes of External Genital Warts

Abstract: To determine whether men are able to self-diagnose external genital warts (EGWs), we studied data from 1115 men with and without human immunodeficiency virus infection. Men were largely unable to accurately assess the presence of EGWs. Self-reporting of EGWs was not a sensitive tool; only 38% of men who had EGWs diagnosed by a trained examiner who used bright light and visual inspection also reported having them. When we controlled for other covariates in a multivariate model, men who had EGWs diagnosed by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We only had information about age in nonparticipants, and in all 4 countries the age distribution was very similar to that among the participating women (data not shown). In addition, the accuracy of selfreported genital warts has been questioned but is largely unknown [27], and, in the United Kingdom, where STIs are routinely registered, a high consistency has been found between population rates and self-reported behavior [28]. However, in one study, it was found that the concordance between selfreported genital warts and a medical examiner's finding increased if the person had had a previous episode of genital warts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only had information about age in nonparticipants, and in all 4 countries the age distribution was very similar to that among the participating women (data not shown). In addition, the accuracy of selfreported genital warts has been questioned but is largely unknown [27], and, in the United Kingdom, where STIs are routinely registered, a high consistency has been found between population rates and self-reported behavior [28]. However, in one study, it was found that the concordance between selfreported genital warts and a medical examiner's finding increased if the person had had a previous episode of genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…Women who had moved or emigrated, who had died before our contact, or who did not speak the respective Nordic language were ineligible for the study, leaving 27,272 Data collection. To guarantee confidentiality for the participants, all invited women were appointed a unique study number by the national study centers.…”
Section: Study Populationmentioning
confidence: 99%
“…In mild cases, patients with anogenital warts may be unaware of their presence-surprisingly, the self-reporting of anogenital warts is not a sensitive tool for diagnosis. [44][45][46] For example, Wiley et al 46 found that only 38% of men who had external anogenital warts diagnosed by a trained examiner using bright light and visual inspection also self-reported having anogenital warts. 46 In practice, patients with a low wart burden and a higher likelihood of natural clearance may not seek physician care, while individuals with the largest and most extensive warts are more likely to seek treatment.…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…If the patient and clinician opt for home-based treatment, patients should be reassessed to evaluate success of treatment via skilled visual inspection with bright light and magnification (level III evidence), because self-reporting of whether treatment has been effective may be inaccurate and result in incomplete clearance with subsequent recurrence. 9,10 Imiquimod. While most therapies, both patientand provider-administered, rely on the physical destruction of lesions, imiquimod is a patientapplied cream that acts through immunomodulatory effects and is directed at the eradication of HPV, the causative agent of condylomata.…”
Section: Patient-applied Treatment Modalitiesmentioning
confidence: 99%